A phylogenetic approach to the Philippines endemic centipedes of the genus Scolopendra Linnaeus, 1758 (Scolopendromorpha, Scolopendridae), with the description of a new species - Doménech, Carles; Barbera, Victor M.; Larriba, Eduardo (Zootaxa, 2018)
The genus Scolopendra Linnaeus, 1758 is represented in the Philippines’ fauna by five species, two of which are endemic. Mitochondrial DNA sequences of gene cytochrome c oxidase subunit I (COI) were obtained from six Scolopendra specimens belonging to two endemic species and a new one, described here as Scolopendra paradoxa Doménech sp. nov. These sequences were analyzed together with another forty-one sequences from GenBank, including additional species of Scolopendra and a few representatives of other Scolopendridae genera. Phylogenetic trees inferred from the COI analysis using maximum likelihood and neighbor joining showed the three Philippines Scolopendra endemic species as a polyphyletic group coherent with their respective morphologies, although the position of S. spinosissima Kraepelin, 1903 varied within the obtained trees. Species delimitation based on standard external morphological characters was also concordant with the observed genetic distances, monophyly and node support, confirming S. subcrustalis Kronmüller, 2009 and S. paradoxa sp. nov. as separate species also at the molecular level, while only the position of S. spinosissima could not be properly established with any of the statistical methods used. In addition, the male genitalia of the three studied species were found to lack gonopods and a penis. Remarks on the ultimate legs prefemoral spinous formula of S. spinosissima plus a key to the species of the genus Scolopendra in the Philippines are provided.